“Physician, heal thyself” (Luke 4:23). Professor S. V. Troitsky against the “eastern papacy” of Constantinople - Andrey Kostryukov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Sergei Victorovich Troitsky is a prominent theologian and canonist, doctor of theology of the University of Belgrade. Heritage of this scholar is in demand now, though many of his articles are not known to the reading public. The letter which is published here belongs to an important event in the history of the church. In 1965, patriarch Athenagoras (Spyrou) of Constantinople excluded from his jurisdiction the Exarchate of Russian Orthodox Parishes of Western Europe which was ruled by archbishop Georgy (Tarasov). In patriarch Athenagoras’ proclamation, there was advice for archbishop Georgy to go over under the authority of patriarch of Moscow Alexy I. It might have seemed that this event was an important victory of Moscow diplomacy. However, contemporaries, S. V. Troitsky among them, paid attention to the formulations of the proclamation of Constantinople Patriarchy. According to these formulations, Constantinople established its rights upon the diaspora in the whole world. Troitsky in his letter to Metropolitan Nikodim (Rotov), head of the Department for External Church Relations, makes a point that these claims of Constantinople are unfounded. Besides, he mentions the danger of the new policy of Phanar. For example, for the Orthodox it will be harder to have a dialogue with Anglicans and Old Catholics, who left Roman Church just because of its claims for global power. Now the same situation takes place in the Orthodox Church as well. Troitsky proposed to prepare a brochure with criticism against the policy of Constantinople. Such a brochure would be useful because Troitsky’s articles on this topic were scattered in various foreign journals and had been forgotten by that time. Troitsky also discusses canonic measures that should be taken against archbishop Georgy (Tarasov), who refused to affi liate with the Moscow Patriarchate.